NP

Tính B = 1.2.3 + 2.3.4 + ... + (n - 1)n(n + 1)

giúp mk làm bài này với mk tk cho!!

NU
11 tháng 4 2020 lúc 21:59

B = 1.2.3 + 2.3.4 + ... + (n - 1)n(n + 1)

4B = 1.2.3.4 + 2.3.4.4 + ... + (n - 1)n(n + 1).4

4B = 1.2.3.4 + 2.3.4.(5 - 1) + 3.4.5.(6 - 2) + .... + (n - 1).n.(n + 1).[(n + 2) - (n - 2)]

4B = 1.2.3.4 + 2.3.4.5 - 1.2.3.4 + 3.4.5.6 - 2.3.4.5 + ... + (n-1)n(n+1)(n+2) - (n-2)(n-1)n(n+1)

4B = (n-1)n(n+1)(n+2)

B = (n-1)n(n+1)(n+2) : 4

Bình luận (0)
 Khách vãng lai đã xóa
H24
12 tháng 4 2020 lúc 6:46

Ta có : 4B =4 . ( 1.2.3 + 2.3.4 + ...+ (n - 1 )n( n + 1 )

<=> 4B = 1.2.3 .( 4 - 0 ) + 2.3.4 .( 5- 1 ) + ... + ( n - 1 ) n ( n + 1 ) [ ( n + 2 ) - ( n - 2 ) ]

<=> 4B = 1 . 2 . 3 . 4 +2 . 3. 4 .5 -1.2.3 .4 + ... + ( n- 1 ) n ( n + 1 ) ( n + 2 )- ( n-1)( n+1).n/( n- 2 )

<=> 4B = ( n-  1 ).( n+1 ).n.( n + 2 )

<=> B = \(\frac{\left(n-1\right)\left(n+1\right)n\left(n+2\right)}{4}\)

Vậy B = \(\frac{\left(n-1\right)\left(n+1\right)n\left(n+2\right)}{4}\)

Bình luận (0)
 Khách vãng lai đã xóa

Các câu hỏi tương tự
ST
Xem chi tiết
FY
Xem chi tiết
TD
Xem chi tiết
KH
Xem chi tiết
AB
Xem chi tiết
H24
Xem chi tiết
NG
Xem chi tiết
LG
Xem chi tiết
MN
Xem chi tiết